2022
DOI: 10.3390/su15010146
|View full text |Cite
|
Sign up to set email alerts
|

Parks, Green Space, and Happiness: A Spatially Specific Sentiment Analysis Using Microblogs in Shanghai, China

Abstract: Green spaces, particularly urban parks, provide essential environmental, aesthetic, and recreational benefits to human health, well-being, and happiness. However, traditional forms of investigating people’s perceptions of urban parks, such as questionnaires and interviews, are often time- and resource-intensive and do not always yield results that are transferable across sites. In this study, spatially explicit geolocational information (Sina Weibo check-in data) was utilized to analyze expressions of happines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 113 publications
1
3
0
Order By: Relevance
“…Secondly, the results show that urban designs reflecting quality of design, ease of use, and accessibility are more valued. These findings are aligned with previous research work by [54], which states that the frequent use of urban green spaces is associated with their accessibility and level of naturalness. In fact, the results demonstrate that these characteristics are more valued than the provision of ecosystem services when assessing the preference for a green space.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, the results show that urban designs reflecting quality of design, ease of use, and accessibility are more valued. These findings are aligned with previous research work by [54], which states that the frequent use of urban green spaces is associated with their accessibility and level of naturalness. In fact, the results demonstrate that these characteristics are more valued than the provision of ecosystem services when assessing the preference for a green space.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, at present, more and more research not only focuses on the accessibility of park services but also on many other social benefits brought by park services, such as accessibility and public health [38][39][40], accessibility, and environmental justice [41]. Researchers found that urban parks reduce the risk of chronic diseases such as obesity and cardiovascular diseases by providing outdoor fitness venues [42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the urban form, landscape, and climate environment have significant influences on public emotions ( Leyden et al, 2011 ; Mouratidis and Hassan, 2020 ). For example, researchers observed that good spatial accessibility ( Lai and Deal, 2022 ; Sun et al, 2023 ), ample and high-quality urban greenery ( Huai and Van De Voorde, 2022 ), and a good visibility of blue and green spaces ( Qiang et al, 2019 ) in the city can help trigger people’s positive emotions. In contrast, unfavorable climate conditions, such as drought, heat waves, and heat island, can lead to negative public emotions ( Fritze et al, 2008 ; Holly et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%